Radicals in exile : English Catholic books during the reign of Philip II - Domínguez, Freddy Cristóbal, 1982- (Iberian encounter and exchange, 475-1755, 2020)
"Examines how English Catholic exiles in Spain used print and other written media to promote the conquest of England and the spiritual renewal of Christendom"--